2024
DOI: 10.3390/app14052042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fracture Characteristics and Crack Propagation Mechanism of Fractured Sandstone under Dynamic Loading

Qi Ping,
Xiangyang Li

Abstract: In order to study the impact of fracture thickness on the dynamic mechanical properties of rock specimens, impact compression tests on prefabricated sandstone specimens with different fracture thicknesses and intact specimens were carried out by using a split Hopkinson pressure bar (SHPB) test device, and the dynamic mechanical parameters of the fractured sandstone specimens were obtained. The results showed that the dynamic stress–strain curves of the prefabricated fractured sandstone specimens are similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…By combining XRD and SEM scanning electron microscopy, a deeper understanding of the changes in the pore structure characteristics of tight sandstone under the composite action of acidification and supercritical CO 2 can be achieved by comparing untreated and singly treated sandstones. Following this, uniaxial compression tests were conducted on the rock samples to analyze the changes in their mechanical properties [24]. Previous studies have shown that both acid treatment and supercritical CO 2 soaking can alter the pore structure and mechanical properties of rocks.…”
Section: Introductionmentioning
confidence: 99%
“…By combining XRD and SEM scanning electron microscopy, a deeper understanding of the changes in the pore structure characteristics of tight sandstone under the composite action of acidification and supercritical CO 2 can be achieved by comparing untreated and singly treated sandstones. Following this, uniaxial compression tests were conducted on the rock samples to analyze the changes in their mechanical properties [24]. Previous studies have shown that both acid treatment and supercritical CO 2 soaking can alter the pore structure and mechanical properties of rocks.…”
Section: Introductionmentioning
confidence: 99%